Foreign Direct Investment, Domestic Investment and Economic Growth: Evidence from ASEAN-5 - Almasaied, Suliman Warred (2004)
This study is an empirical analysis of the impact of domestic investment and FDI on the economic growth of ASEAN-5 namely Indonesia, Malaysia, the Philippines, Thailand and Singapore during the last four decades. Also the study focuses on the FDI inflow into ASEAN-5, and the domestic investment accumulation process in the ASEAN-5. This research was conducted following recent events such as the decline in the inflow of foreign capital and growth rates of domestic investment and thereafter the economic growth after the Asian financial crisis, and the search for new policy options that could contribute to sustained economic growth. The growth and FDI models for this study are derived from the endogenous growth model, which can explain the behaviour of ASEAN-5 economies. The theoretical models are based on the previous works of Romer (1991), and developed by Borensztein, e. al. (1998). The domestic investment equation is derived based on the flexible accelerator model, which is an extension of a model established by Fry (1998) and developed by Agrawal (2000a, 2000b). This study utilized the autoregressive distributed lag approach to cointegration (ARDL) developed by Pesaran et al. (1996, 2001). This technique has additional advantages of yielding consistent estimates of the long-run coefficients. It is also free of residual correlation, and can distinguish between dependent and explanatory variables. The major findings of this study can be summarized as follows: (i) domestic investment, FDI, and financial intermediation significantly affect the economic growth of ASEAN-5; (ii) FDI has positive and significant effect on domestic investment and vice-versa. ; (iii) the improvement in the development level of financial intermediation and human capital has a vital role on ASEAN-5’s economic growth through FDI and domestic investment channels; (iv) the growth rate of GDP and domestic investment significantly affect FDI inflows to ASEAN-5; (v) outward-looking together with stable exchange rate policies contribute positively to both FDI and domestic investment and thereafter economic growth; (vi) the results reveal that ASEAN-5 can rely on domestic resources such as investment, saving, human capital, financial intermediation as instruments of economic growth, and FDI alone may not be able to sustain economic growth. Hence, economic growth based on domestic resources should be encouraged.